2017
DOI: 10.1016/j.ejphar.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of cGMP in early sepsis

Abstract: Septic shock, which is triggered by microbial products, is mainly characterised by inadequate tissue perfusion, which can lead to multiple organ dysfunction and death. An intense release of vasoconstrictors agents occurs in the early stages of shock, which can lead to ischemic injury. In this scenario, cGMP could play a key role in counterbalancing these agents and preventing tissue damage. Sildenafil, which is a phosphodiesterase-5 inhibitor, increases cGMP in smooth muscle cells and promotes vasodilation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
11
1
4
Order By: Relevance
“…In 2017, other groups confirmed the effects of PDE5 inhibitors. Kovalski et al confirmed the protective effect of sildenafil in the rat CLP model of sepsis featuring significantly increased levels of plasma nitrate/nitrite (NO x ), aspartate aminotransferase (AST), alanine aminotransferase (ALT), urea, creatinine, creatine kinase and lactate [79]. At a functional level, the sepsis led to hypotension, hyporesponsiveness to vasoconstrictor, and renal blood flow reduction.…”
Section: Sildenafil and Phosphodiesterase-5 Inhibitorsmentioning
confidence: 93%
“…In 2017, other groups confirmed the effects of PDE5 inhibitors. Kovalski et al confirmed the protective effect of sildenafil in the rat CLP model of sepsis featuring significantly increased levels of plasma nitrate/nitrite (NO x ), aspartate aminotransferase (AST), alanine aminotransferase (ALT), urea, creatinine, creatine kinase and lactate [79]. At a functional level, the sepsis led to hypotension, hyporesponsiveness to vasoconstrictor, and renal blood flow reduction.…”
Section: Sildenafil and Phosphodiesterase-5 Inhibitorsmentioning
confidence: 93%
“…Nevertheless, PDE5 inhibitors have been effective in the indirect lung injury, as well. In a model of CLP-induced sepsis in rats, administration of sildenafil 8 h after the insult elevated a renal blood flow and decreased the plasma levels of creatinine, lactate, and creatine kinase, and lung myeloperoxidase [171]. In acute pancreatitis-associated ALI in rats sildenafil reduced an extent of the lung injury and inflammation, elevated an expression of proliferation-related markers, and suppressed an expression of apoptosis-related markers [172].…”
Section: Pde5 Inhibitorsmentioning
confidence: 98%
“…Depois disso, o paciente passa para um estágio imunossuprimido (Kumar, 2020;Coopersmith et al, 2018). O sistema circulatório também sofre mudanças durante a sepse e choque séptico, passando de uma vasoconstrição inicial intensa para vasodilatação generalizada que pode não responder a vasoconstritores naturais, gerando hipotensão e hipoperfusão (Kovalski et al, 2017;Russell, Rush & Boyd, 2018).…”
Section: Fisiopatologiaunclassified
“…Esses nucleotídeos são metabolizados pelas enzimas fosfodiesterases (PDE), a qual é dividida em 11 famílias com diferentes especificidades de substrato. Diante disso, a inibição da PDE pode ser uma estratégia para prevenir lesão isquêmica e diminuir a resposta inflamatória em pacientes sépticos (Kovalski et al, 2017;Pan et al, 2019).…”
Section: Introductionunclassified
See 1 more Smart Citation